2014
DOI: 10.1016/j.drugalcdep.2014.07.020
|View full text |Cite|
|
Sign up to set email alerts
|

Utilization and outcomes of detoxification and maintenance treatment for opioid dependence in publicly-funded facilities in California, USA: 1991–2012

Abstract: Background California treats the largest population of opioid dependent individuals in the US and is among a small group of states that applies regulations for opioid treatment that are more stringent than existing federal regulations. We aim to characterize changes in patient characteristics and treatment utilization over time, and identify determinants of successful completion of detoxification and MMT retention in repeated attempts. Methods State-wide administrative data was obtained from California Outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 25 publications
0
56
0
1
Order By: Relevance
“…Fifteen-year follow-up data from a small group of Swedish methadone patients indicate that an opiate-free life can be achieved [43], but most studies agree that opioid-dependent patients with and without maintenance therapy have a high risk for inpatient treatments and detoxification [44]. An important 15-year follow-up of an Israeli sample ( n = 613), published by Peles et al [6], found that patients staying longer in treatment had a lower mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen-year follow-up data from a small group of Swedish methadone patients indicate that an opiate-free life can be achieved [43], but most studies agree that opioid-dependent patients with and without maintenance therapy have a high risk for inpatient treatments and detoxification [44]. An important 15-year follow-up of an Israeli sample ( n = 613), published by Peles et al [6], found that patients staying longer in treatment had a lower mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged retention in treatment typically results in reductions in illicit drug use, behaviors that increase the risk of contracting HIV, and criminal activity (Amato et al, 2005). There is evidence that prescription opioid users are more likely to respond and be retained in OAT compared to heroin users (Moore et al, 2007; Nosyk et al, 2014; Soeffing et al, 2009). Discontinuing treatment typically results in relapse and elevated risk of mortality, with the risk of death after discontinuing treatment estimated to be 2.4 times greater than during treatment (Degenhardt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Critically, these gains were only observed in a subset of 61% of the study cohort, with 20% demonstrating no HRQoL response despite sustained engagement in treatment (Nosyk et al, 2011). Furthermore, an increasing proportion of OAT clients in the US are presenting with PO dependence (Nosyk et al, 2014), often receiving buprenorphine treatment in office-based settings (Kleber, 2008) in either time-limited (i.e., detoxification) or time-unlimited treatment regimens. There is a paucity of research on the potential differential effects on HRQoL of disparate treatment modalities, or whether greater gains are achievable in PO dependence compared to heroin dependence, considering the latter may be associated with more concurrent medical problems such as hepatitis C (Suryaprasad et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Screening tools and PDMPs that track opioid use should be carefully integrated into efforts to enhance the safety and delivery of opioids [7578]. In addition, and similar to findings from Drossman et al [67], other studies evaluating opioid detoxification programs have yielded modest results and call into question the longer-term effectiveness of detoxification [7980]. Interventions that build on patient self-management to reduce opioid use, however, have shown particular promise among patients with chronic pain [8182], and as shown by Bocelli et al [69] and Meana et al [70], may be useful to reduce opioid misuse in chronic pancreatitis and other chronic GI symptoms and disorders.…”
Section: Discussionmentioning
confidence: 98%